Systemic modeling of the free energy of soil water; adequacy with the Carnot cycle and Clausius inequality - Braudeau, Erik (European Journal of Applied Sciences, 2022)
In classical thermodynamics, entropy and temperature are two associated thermodynamic variables whose dimensional equations are unknown but whose product is, like heat, energy (ML2T-2). By taking the first thermodynamic concepts of the physicochemists who followed the Gibbs school and adapting them to the theory of hierarchical systems practiced in hydrostructural pedology, we finally resulted in the systemic modeling of the thermodynamics of the fluid phases of the natural environment and in particular of the soil water. By developing this systemic model hierarchically down to the molecular and atomic organization levels of the fluid phases of the pedostructure, we were able to recognize the dimensional identities of all the thermodynamic variables appearing at the different levels of soil organization with the water and air, including those 2 levels of molecular and atomic organization that had never been considered before. This leads us to reconsider the second law of thermodynamics at a more fundamental organizational level than it is currently applied, namely the level of molecular organization, both internal and external to the molecule (in the phase), where the first process of thermodynamic equilibrium occurs. With this new point of view, the Carnot cycle explicitly confirms the correspondence between the traditional thermodynamic terminology and the systemic variables and equations of the new thermodynamics model. However, a completely different interpretation of the Carnot cycle is highlighted here that no longer has anything to do with the notion of reversibility/irreversibility but instead with the notion of thermodynamic equilibrium and of stability of this equilibrium. New fields of research are opening up in perspective.